How to intensify research & publications for academicians - Abdullah, Moha Asri (2018)
Conduct research and publish articles are not an easy task. The proper plan and systematic execution are much needed. Simultaneously, the demand for academicians to carry out these tasks is on the rise and expectation from employers in terms of Key Performance Index are getting higher and higher over the year. This public lecture addresses this issue by emphasizing certain approach, plan, and execution. From the research perspective, there are five major that are highly essential for academicians to observe and set their journey on it. These include, niche area research approach, collaborative approach, student research approach, angel research approach and pipeline research approach. The output shall target publication in high impact journal.